The systemic model of learning and teaching, as support in the labor insertion - Corcino-Barrueta, Fernando E. (2021)
The main objective of the research was to find out how the systemic process influences with the teaching and learning approach, in the labor inclusion of graduates of the Faculty of Law of the National University Hermilio Valdizán. To achieve this, the study was developed based on a descriptive explanatory type, under a non-experimental, correlational and cross-sectional design, for which we worked with a population of 121 graduates and the sample consisted of 37 graduates from the years 2016 and 2017, being of the non-probabilistic type, which were constructed two questionnaires, a questionnaire to measure the systematic teaching-learning process variable, another questionnaire to measure the job placement opportunity variable, all to qualify the level of influence. Sperman's Ro test was applied to evaluate the hypothesis. As a result, our results confirmed the study hypothesis, showing that the systemic teaching-learning process shows a significant relationship with job placement and that there is a positive influence between both variables. Reaching the conclusion that exercising a systemic process in teaching and learning generates opportunity in labor inclusion.